The Quality Mental Health Care Network: A roadmap to improving quality mental healthcare in Canada. Issue 2 (March 2021) - Follwell, Emily J.; Chunduri, Siri; Samuelson-Kiraly, Claire; Watters, Nicholas; Mitchell, Jonathan I.
Although there are numerous quality of care frameworks, little attention has been given to the essential concepts that encompass quality mental healthcare. HealthCare CAN and the Mental Health Commission of Canada co-lead the Quality Mental Health Care Network (QMHCN), which has developed a quality mental healthcare framework, building on existing provincial, national, and international frameworks. HealthCare CAN conducted an environmental scan, key informant interviews, and focus groups with individuals with lived experiences to develop the framework. This article outlines the findings from this scan, interviews and focus groups.